Evolution of land use environmental impact of eucalyptus globulus in the context of life cycle assessment - José Vicente Ferreira; Bruno Esteves; Idalina Domingos (Instituto Politécnico de Viseu, 2022)
Introduction: The eucalyptus globulus forest area in Continental Portugal has shown a systematic increase over the last 50 years. In 20015 it was the species with the highest forest land occupation representing 26.2% of the total Portuguese forest area. Although between 2005 and 2015 the occupation of the soil by eucalyptus globulus had grown about 7.5%, the existing volume increased slightly 0.2%. The wildfires had a strong impact on this with a total burnt area of 1.1 million hectares during this period. Objective: Due to its economic value (national leader in exports of high added value) and social (contributes to the generation of thousands of jobs) this study aims to assess the evolution of the environmental impact of eucalyptus globulus on the land use between 2005 and 2015. Methods: The life cycle assessment methodology is followed and the ILCD 2011 Midpoint+ method available in the SimaPro software was chosen to assess the land use environmental impact. Results: Land use impact category of 1 m3 of eucalyptus globulus trees, standing, in forest, was 21832 Kg C deficit in 2005 and 23430 Kg c deficit in 2015 that means an increased about 7.3% during this period. Conclusion: Transformation to forest road (from natural forest) is the process that most contributes for the land use impact with approximately 78%. Forest occupation is the second most important process representing about 19.5% of the total impact category and forest road occupation represents only 3%.